Current state of research on testicular microlithiasis: A bibliometric analysis of the last five years’ scientific literature. - Nieto Muñoz, Santiago; Calderon Marin, Sarah; Osorio Beltran, Daniela Alejandra; Girardot Camargo, Diana Marcela; DÃaz Vallejo, Jhony Alejandro; Cuji Galarza, Wendy Dayanna; Melo, Isabel Alejandra (Revista científica estudiantil 2 de Diciembre, 2023)
SUMMARY Introduction: TM presents an incidence up to 2% in the pediatric population, a higher incidence is also presented in patients with underlying pathologies such as Klinefelter Syndrome and Down Syndrome. Its presence is associated with other tumor pathologies that affect patients’ life quality. Methods: a bibliometric analysis was carried out using the available information in 3 databases to evaluate the current state of research on testicular microlithiasis worldwide. ScienceDirect, Scopus and PubMed were reviewed, using the terms "testicular microlithiasis" and "child", combined with Boolean operators, in articles published from 2018 until 2022. Results: 131 articles related to testicular microlithiasis had been published in the ScienceDirect (n=79), Scopus (n=35) and PubMed (n=17) databases in the last five years. United States, Turkey and China were the countries that achieved most of the publications about TM. The journals with the highest number of publications in ScienceDirect were Journal of Pediatric Urology, Journal of Pediatric Surgery, and Surgical Pathology. The most divulged type of publication in ScienceDirect are book chapters, while in PubMed and Scopus are original articles. Conclusions: research on TM in Latin America has been scarce and that at a global level it is not very significant in terms of the number of studies that are carried out and are published in indexed journals in despite of the high percentage of this finding in routine testicular ultrasounds in the pediatric population (10%) and its association with both benign and malignant pathologies that affect the life and prognosis of patients.